Differences in oxidative stress across seasons and ability to cope with environmental mismatch in muscle and brain of black-capped chickadees (Poecile atricapillus) and rock pigeons (Columba livia) - Jimenez, Ana; Tobin, Kailey; McCann, MaryKathryn; Briggs, Christopher (Dryad, 2020)
Resident birds in temperate areas respond to seasonally fluctuating
temperatures by adjusting their physiology so as to match thermogenic
requirements of their environment. Climate change is predicted to increase
the frequency of heat waves, increasing the likelihood that birds will
face environmental mismatch. Changes in BMR due to seasonality or anomaly
events should show effects to the oxidative stress system. We examined the
effects of chronic and acute heat exposure on muscle and brain tissue
total antioxidant capacity, enzymatic activities of catalase (CAT), and
glutathione peroxidase (GPx) and lipid peroxidation (LPO) damage in two
temperate bird species of differing body masses and ecological strategies,
the black-capped chickadee (Poecile atricapillus) and the rock pigeon
(Columba livia), across three seasons. We found that heat stress did not
alter oxidative stress in either species or tissue. But, in muscle, rock
pigeons and black-capped chickadees demonstrated similar seasonal changes
where peroxyl scavenging capacity was highest in the fall, hydroxyl
scavenging capacity was higher in fall and summer. CAT activity was lowest
in the fall and highest in the summer, GPx activity was highest in the
fall, and LPO damage was highest in the summer but lowest in the
fall.  In brain, we found that scavenging capacity to hydroxyl
radicals was highest in fall and summer for rock pigeons, whereas it was
only elevated in the summer for black-capped chickadees. Our data suggest
that the oxidative stress system is slow to change seasonally.
Keywords: black-capped chickadee; Poecile atricapillus; rock pigeon; Columba livia; oxidative stress